Pengaruh Influencer, Content Marketing, Dan Desain Produk Terhadap Keputusan Pembelian Pada Produk Beauty And Care (Studi Kasus Pada Konsumen Produk Beauty And Care Di Kota Malang) - Anandiya, Khofifah Eka; Khalikussabir, Khalikussabir; Rachmadi, Kartika Rose (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study is to see how elements of marketing strategy influence purchasing decisions among consumers in Malang City when buying beauty and care products. The variables studied include influencers, content marketing, and product design. Influencers, content marketing, and product design can have an impact on purchasing decisions. This study uses a quantitative methodology to gather information from 100 respondents who use beauty and care products in Malang City. The findings indicate that the decision to purchase beauty and care products is simultaneously influenced by influencers, content marketing, and product design. Meanwhile, partially, influencers and content marketing have a significant negative impact on purchasing decisions, while product design has no effect on purchasing decisions. According to this research, businesses can enhance their marketing tactics to gain customer trust and emphasize the high-quality materials or ingredients used in the production of their products. Keywords: Influencer, Content Marketing, Product Design, Purchase Decisions, Beauty and Care